(untitled) (Journal of Veterinary Medicine and Animal Production, 2022)
This study aimed to study marketing strategies adopted by small scale private Ice-cream shops in Khartoum Sudan. The study was based on primary data collection using a scientifically structured questionnaire that targeted senior managers in Ice cream investments. A stratified sampling was performed where all shops that met the criteria of stratification were put under study. The sample included 30 shops located in different geographical areas in Khartoum. Collected data was analyzed using the SPSS program to obtain the frequency of distributions, and Chi- square values. Main results obtained showed that most of the shops 83.3% possessed a logo that resembled their brand; 91.7% of Ice-cream shops’ managers stated that they innovated in their product; 66.7% set their price in accordance to the current market prevailing price; 58.3% used social media for promotion and 41.7% considered Facebook as the most important social platform. The study was concluded with recommendations that address current and future aspects in the relevant field where the use ofplanned product innovation and digital marketing could be the key factors for business success and sustainability.